Penicillium marneffei infection and recent advances in the epidemiology and molecular biology aspects - Nongnuch Vanittanakom (2018)
Penicillium marneffei infection is an important emerging public health problem, especially among patients infected with human immunodeficiency virus in the areas of endemicity in southeast Asia, India, and China. Within these regions, P. marneffei infection is regarded as an AIDS-defining illness, and the severity of the disease depends on the immunological status of the infected individual. Early diagnosis by serologic and molecular assay-based methods have been developed and are proving to be important in diagnosing infection. The occurrence of natural reservoirs and the molecular epidemiology of P. marneffei have been studied; however, the natural history and mode of transmission of the organism remain unclear. Soil exposure, especially during the rainy season, has been suggested to be a critical risk factor. Using a highly discriminatory molecular technique, multilocus microsatellite typing, to characterize this fungus, several isolates from bamboo rats and humans were shown to share identical multilocus genotypes. These data suggest either that transmission of P. marneffei may occur from rodents to humans or that rodents and humans are coinfected from common environmental sources. These putative natural cycles of P. marneffei infection need further investigation. Studies on the fungal genetics of P. marneffei have been focused on the characterization of genetic determinants that may play important roles in asexual development, mycelial-to-yeast phase transition, and the expression of antigenic determinants. Molecular studies have identified several genes involved in germination, hyphal development, conidiogenesis, and yeast cell polarity. A number of functionally important genes, such as the malate synthase- and catalase-peroxidase protein-encoding genes, have been identified as being upregulated in the yeast phase. Future investigations pertaining to the roles of these genes in host-fungus interactions may provide the key knowledge to understanding the pathogenicity of P. marneffei. Copyright © 2006, American Society for Microbiology. All Rights Reserved.